Interorganizational Imitation and Acquisitions of High-tech Ventures - Ozmel, Umit; Reuer, Jeffrey J.; Wu, Cheng-Wei (Strategic Management Journal, 2017)
[Research summary: This article shows that there is a positive association between the changes in the number of prior acquisitions or the changes in the prominence of prior acquirers within the focal venture’s subfield and the venture’s likelihood to be acquired. Results are in line with the existence of frequency- and trait-based imitation in acquisitions targeting tech ventures. More importantly, these positive associations are more pronounced when (a) exogenous technological uncertainty within the venture’s subfield increases and (b) there are significant differences between the focal venture’s and acquirer’s technological resources. Our findings are in accord with the suggestion that uncertainty in the technology domain is an important boundary condition in moderating the extent of imitation in technology acquisitions. We also discuss alternative explanations and implications. Managerial summary:The findings of this article suggest that when deciding whether or not to acquire a technology venture (i.e., startup company in a high-tech industry), managers infer information by observing other acquisitions in the venture’s subfield to make assessments about the underlying value of the potential targets. We also find that receiving some informational cues from previous acquisitions would be more useful when there is high technological uncertainty in the potential target’s subfield about which technologies will be dominant, and when the potential acquirer and the tech venture operate in dissimilar technological areas. This article shows that imitation can be one way to deal with decision-making under uncertainty when making acquisition decisions in high-tech environments.]